2014
DOI: 10.1136/bmjspcare-2014-000654.198
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Prescribing of Opiates and Sedatives at End of Life in a Large District General Hospital

Abstract: Background The review of the LCP included concerns that opiates and sedatives had been used inappropriately at end of life. Although studies of prescribing for hospice inpatients concluded safe practice and lack of evidence that their use shortens survival, there is a lack of studies examining similar aspects of prescribing in hospital inpatients. Aims The aims of the audit were to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…5 Philips et al found that the doses of opioids and sedatives given to patients on the LCP in a large district general hospital in the United Kingdom were safe and not unduly increased. 6 A survey of health care providers working in a U.K. hospital setting found that the majority of staff were able to recognize when to start LCP and decide on the appropriate monitoring and treatment. 7 However, a cluster randomized trial done by Costantini et al showed no improved benefit in overall quality of care when LCP was in use.…”
Section: Introductionmentioning
confidence: 99%
“…5 Philips et al found that the doses of opioids and sedatives given to patients on the LCP in a large district general hospital in the United Kingdom were safe and not unduly increased. 6 A survey of health care providers working in a U.K. hospital setting found that the majority of staff were able to recognize when to start LCP and decide on the appropriate monitoring and treatment. 7 However, a cluster randomized trial done by Costantini et al showed no improved benefit in overall quality of care when LCP was in use.…”
Section: Introductionmentioning
confidence: 99%